2016
DOI: 10.1371/journal.pone.0164921
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Nomogram for Predicting Survival Outcomes in Early Mucinous Breast Cancer

Abstract: BackgroundThe features related to the prognosis of patients with mucinous breast cancer (MBC) remain controversial. We aimed to explore the prognostic factors of MBC and develop a nomogram for predicting survival outcomes.MethodsThe Surveillance, Epidemiology, and End Results (SEER) database was searched to identify 139611 women with resectable breast cancer from 1990 to 2007. Survival curves were generated using Kaplan-Meier methods. The 5-year and 10-year cancer-specific survival (CSS) rates were calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 29 publications
5
41
0
Order By: Relevance
“…Several studies have indeed shown a worse survival in colorectal MACs 6 , 7 , whereas others did not identify any adverse prognostic effect 8 , 9 . However, for mucinous breast cancer, nearly all studies uniformly reached the same conclusion, suggesting that individuals with this cancer type have a better outcome than patients with infiltrating ductal carcinoma 10 12 . Debates have persisted regarding the relationship between the primary tumor site and cancer-specific survival in MAC cases.…”
Section: Introductionmentioning
confidence: 90%
“…Several studies have indeed shown a worse survival in colorectal MACs 6 , 7 , whereas others did not identify any adverse prognostic effect 8 , 9 . However, for mucinous breast cancer, nearly all studies uniformly reached the same conclusion, suggesting that individuals with this cancer type have a better outcome than patients with infiltrating ductal carcinoma 10 12 . Debates have persisted regarding the relationship between the primary tumor site and cancer-specific survival in MAC cases.…”
Section: Introductionmentioning
confidence: 90%
“…Mucinous breast carcinoma (MBC), a type of breast cancer characterized by a large amount of extracellular mucin, has a reported incidence ranging from 1–7% among all primary breast cancers . MBC presents favorable clinical and pathologic characteristics in terms of hormone receptor status, tumor grade, and lymph node (LN) involvement and is characterized by a favorable prognosis and excellent long‐term survival …”
mentioning
confidence: 99%
“…cer characterized by a large amount of extracellular mucin, has a reported incidence ranging from 1-7% among all primary breast cancers. [1][2][3][4] MBC presents favorable clinical and pathologic characteristics in terms of hormone receptor status, tumor grade, and lymph node (LN) involvement 5 and is characterized by a favorable prognosis and excellent longterm survival. 6,7 MBC is further divided into pure MBC (PMBC) and mixed MBC (MMBC) subgroups according to the quantification of tumor cellularity by the World Health Organization (WHO).…”
mentioning
confidence: 99%
“…PMC generally shows favorable prognosis. However, some studies reported that ER/PR negativity and high grade are associated with a poor prognosis in PMC [11,12].…”
Section: Discussionmentioning
confidence: 99%